Why shorten calving intervals on smallholder dairy farms in East Africa? - Tanner, J.C.; McCarthy, N.A.; Omore, Amos O. (British Society of Animal Science, 1998)
In European dairy herds lactation curves are conventionally described by a gamma function such as that of Wood (1969). High yields in early lactation mean that more frequent calving leads to increased annual milk production (AMP) per cow. Thus, the optimum calving interval in the UK is 365 days (Esslemont et al, 1985) Studies on smallholder dairy farms in E. Africa (e.g. Omore, 1996; Staal et al., 1997) indicate that a large proportion of high-grade exotic dairy cows display lactations which collapse to a prolonged, but stable profile described by a logarithmic function. Extension services in Kenya recommend that farmers shorten their calving interval (CI) from a current average of 590 days (Staal et al., 1997) to a target of 365 days. Given the absence of high early lactation yields what benefits can be gained from the greater investment required to reduce CI on smallholdings?